(3GdJTQjYGJ GdJLGQjI hJTQjYGJ GdCYeGd (B:s (3dWdHI GdYdhe GdEOGQjI hGdeGdjI (B/s - (3GdShjdejjf, UaGA eMehOs; (3GdThG, JGdG eSYhO s ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2005)
(3GdCMcGe GdYGeI ddbGfhf(B- (3GdJTQjYGJ hGdbhGfjf GdJLGQjI(B- (3GdTQcGJ GdJLGQjI PGJ GdUdI HGdJTQjYGJ GdJLGQjI(B- (3bhGfjf GdYed hGdVeGf GdELJeGYj(B.s
Keywords: (3GdCYeGd GdEOGQjIs; (3GdJLGQIs; (3GdbGfhf GdJLGQjs